Reflections on Asylum Archives and the Experience of Mental Illness in Paris - Prestwich, Patricia (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2012)
This article is a personal reflection on the challenges and rewards of doing research on the social history of mental illness and health. The author uses her experiences with the archives of a Parisian psychiatric hospital to discuss some ways of dealing with an overwhelming mass of archival material and the inevitable frustrations and silences that result from trying to do history from the patient’s point of view. The importance of such archival research on mental illness is discussed within the context of a long history of French efforts to provide health care for “citizen-patients.” The article argues that such archives not only provide a wealth of material on the history of illness but that they offer important perspectives on other political and social issues, including the development of the welfare state, the maintenance of public order, and the varied experiences of citizenship.